Applications of vector analysis and complex variables in engineering - Strack, Otto D. L. (Springer, 2020)
This textbook presents the application of mathematical methods and theorems to solve engineering problems, rather than focusing on mathematical proofs. Applications of Vector Analysis and Complex Variables in Engineering explains the mathematical principles in a manner suitable for engineering students, who generally think quite differently than students of mathematics. The objective is to emphasize mathematical methods and applications, rather than emphasizing general theorems and principles, for which the reader is referred to the literature.